The Conservation of Cultural Heritage and Tourism Industry in Syria by Using Techniques of Geographical Information System (GIS) (Damascus University Journal of Historical Studies, 2023)
Political stability and safety are prerequisites for tourism anywhere in the world. In the Syrian context, the ongoing war against terrorism has had direct and potentially long-term effects, which have prompted tourists to reconsider their decision to travel. This study aimed to put scientific documents in the hands of decision makers in order to reduce the immediate and future impact of the crisis. This study attempts to outline the deeply rooted Syrian historical heritage and the tourism industry before the war. As well as to analyze the current hurdles that have emerged because of the war. It tries to evaluate the effectiveness of the measures taken by the government. The study was based on the descriptive analytical method and historical methodology, the data was analyzed using Excel.  In addition to using Geographical Information System (GIS) for documentation of heritage sites and prepare maps of damaged heritage sites in Syria and heritage sites which damaged  in Aleppo (the most affected city), in addition to developing a map of some religious tourist paths in Syria, in order to reach the desired objectives of the research. The study was concluded that need of measures are proactive. It sees the absence of increasing the awareness of the local community about the value of its heritage as a leading reason of looting and destruction. It also shows the need to direct attention to internal tourism and the importance of attracting tourists from the friendly countries around the world.
Keywords: Tourism; Cultural heritage; Geographical information System; Crisis management; Safeguarding